1979
DOI: 10.1161/01.cir.60.5.1183
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional echocardiographic demonstration of left atrial thrombi in patients with prosthetic mitral valves.

Abstract: Although M-mode echocardiography (MME) is not a reliable method for detecting left atrial thrombi, recent reports suggest that two-dimensional echo (2DE) may be more effective than MME in identifying intracardiac thrombi. In three patients with prosthetic mitral valves who presented with either arterial embolization or prosthetic valvular dysfunction, 2DE demonstrated left atrial masses consistent with thrombi, while MME was either negative (two patients) or suspicious (one patient) for left atrial thrombus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our patient had severe mitral stenosis and moderately severe aortic stenosis of rheumatic origin. Infrequently, ball valve thrombus has been described in patients with mechanical mitral prosthetic valve, 5 bio-prosthetic valve, 6 in isolated severe aortic stenosis, 7 and in patients with no valvular heart disease. 8 The reason for typical spherical shape could be because of fresh clot being layered out concentrically as it spins around the atrium.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had severe mitral stenosis and moderately severe aortic stenosis of rheumatic origin. Infrequently, ball valve thrombus has been described in patients with mechanical mitral prosthetic valve, 5 bio-prosthetic valve, 6 in isolated severe aortic stenosis, 7 and in patients with no valvular heart disease. 8 The reason for typical spherical shape could be because of fresh clot being layered out concentrically as it spins around the atrium.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the routine use of echocardiography, magnetic resonance imaging, or computed tomography permits antemortem diagnosis. Conditions such as atrial fibrillation, mitral stenosis, left atrial dilatation, severe left ventricular dysfunction, and prosthetic mitral valves are associated with a propensity toward left atrial thrombus formation, cardiac embolism or both [4][5][6]. Recently, Acikel et al [7] have reported a freefloating right atrial thrombus in a patient with tricuspid stenosis and atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] This unique motion should serve as a diagnostic aid for the identification of free-floating left atrial thrombi. We recognize the possibility that a dislodged clot or tumor of the left atrial cavity could produce a pattern of mobility as set forth for the free-floating thrombus.…”
Section: Discussionmentioning
confidence: 99%